Dynamic analysis of straight stepped microbeams. (January 2021) - Alcheikh, Nouha; Ouakad, Hassen M.; Younis, Mohammad I.
Abstract: This works aims to investigate the dynamics of Micro-electro-mechanical systems (MEMS) straight multi-stepped micro-beams. An analytical model is presented based on the Euler–Bernoulli beam theory and the Galerkin discretization. The effect of various parameters on the natural frequencies of micro-beams is examined, including the effects of varying the geometry (number of steps and their ratios), the axial force (including those from electrothermal actuation), and the nonlinear electrostatic forces. The analytical results are validated and compared with the simulation results of a Multiphysics Finite-Element (FE) model. Good agreement is found among all the results. The variations of the pull-in and buckling instabilities due to the various parameters are also reported. The results highlight the capability of both passive (geometry) and active (electrostatic and electrothermal/axial) methods to tune the natural frequencies of the structures, which can be useful in applications, such as tunable filters, switches, as well as for creating/avoiding internal resonance and energy exchanges among the various modes. Highlights: Investigated the dynamics of Micro-electro-mechanical systems (MEMS) straight multistepped micro-beams. Analytical model is presented based on the Euler–Bernoulli beam theory and the Galerkin discretization. Analytical model is validated and compared with the simulation results of a Multiphysics Finite-Element (FE) model. Effect of various parameters on the natural frequencies of micro-beams are examined. Variations of the pull-in and buckling instabilities due to the various parameters are also reported. Results highlight the capability of both passive (geometry) and active (electrostatic and electrothermal/axial) methods to tune the natural frequencies of the investigated structure.